EXAMINE THE DETERMINANT FACTORS ON FINANCIAL LEVERAGE OF VIETNAMESE COMMERCIAL BANKS - Dang Nguyen Tuan Kiet; Luu Tien Thuan (International Journal of Accounting, Finance and Business, 2019)
This study aims to explore the determinants of financial leverage in the commercial banks of Vietnam. It also aims at examining the effects of ROE (rate of return on equity) which is an essential factor on financial leverage of Vietnamese commercial banks. In this paper, it is the first time that both ROA (rate of return on assets) and ROE have been put together in the same model to compare their impacts on financial leverage. The study uses the panel data of (24) commercial banks in Vietnam covering the period from 2007 to 2017. Three kinds of econometric model (OLS, FEM, REM) are used in this study. The results indicate that key factors such as fixed asset ratios, ROA, ROE, bank size, GDP growth rate, liquidity are positively related to banks’ financial leverage, whereas, only inflation rate is negatively related to the financial leverage. Ultimately, ROA and ROE have their own roles that they must together appear in the model. ROE can not be replaced by ROA. The study also found that some variables would no longer affect the financial leverage after expanding the sample size by including merged banks and banks that were established after the 2008 global economic crisis. In the first case, if merged banks are included in the sample size, macro factors (inflation rate, GDP growth rate) will not affect the financial leverage of commercial banks. In the second case, the financial leverage of commercial banks is not affected by inflation rate when adding banks that were established after the 2008 into the sample. This paper can make a great contribution in terms of theory and practice to the financial decisions of commercial banks in Vietnam. Not only ROA but also ROE is a trustful index that helps to propose reasonable financial decisions.